Study protocol for “MDMA-assisted therapy as a treatment for major depressive disorder: A proof of principle study” - Kvam, Tor-Morten; Goksøyr, Ivar W.; Stewart, Lowan H.; Repantis, Dimitris; Røssberg, Jan Ivar; Andreassen, Ole A. (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) is a world-leading cause of disability. The available treatments are not effective in all patients, and there is a significant need for more effective treatment options. Here we present the protocol for an investigator-initiated and publicly funded trial of MDMA-assisted therapy (MDMA-AT) for MDD. This single-site, open-label study investigates the proof of principle and safety of MDMA-AT in participants with MDD and provides an initial impression of treatment effectiveness. Methods: A total of 12 participants [>18 years] with DSM-5 diagnosis of MDD will receive a flexible dose of MDMA in a therapeutic setting on two dosing days over a 4 week period preceded by three preparatory sessions. Each MDMA dosing session will be followed by three integration sessions. The primary outcome is change in MDD symptom severity, as measured by the mean change in MADRS scores from Baseline to 8 weeks after the second MDMA session. The secondary outcome is change in functional impairment, as evaluated by the mean change in Sheehan Disability Scale scores from Baseline to 8 weeks after the second MDMA session. Safety measures include vital signs, the incidence of Adverse Events and suicidality as measured by the Colombia-Suicide Severity Rating Scale. Discussion: This proof of principle trial will inform the development of fully powered clinical trials, optimize the protocol for the administration of MDMA-AT in participants with MDD and explore uncertainties including barriers to recruitment, retention and acceptability of MDMA-AT as a treatment for MDD. Clinical Trial Identification: EudraCT number 2021-000805-26 Keywords: MDMA, major depressive disorder, clinical trial, depression, MDMA-assisted therapy